The hybridization work of Mendel, 102 years after Starting the controversy. - Román Bravo, Rafael María; Garcidueñas Piña, Rogelio; Ortiz Rodríguez, Ruy; Atencio León, Atilio Miguel; Yáñez Cuéllar, Luis Fabián; Aranguren Méndez, José Atilio (Revista Científica de la Facultad de Ciencias Veterinarias, 2014)
Â This research was carried out in order to verify by simulation Mendel”™s laws and seek for the clarification, from the author”™s point of view, the Mendel-Fisher controversy. It was demonstrated from: the experimental procedure and the first two steps of the Hardy-Weinberg law, that the null hypothesis in such experiments is absolutely and undeniably true. Consequently, repeating hybridizing experiments as those showed by Mendel, it makes sense to expect a highly coincidence between the observed and the expected cell frequencies. By simulation, 30 random samples were generated with size equal to the number of observations reported by Mendel for his single trait trial, in this case, seed shape; assuming complete dominance, with genes A and a; likewise, it was simulated the results for the experiment with two traits, segregating in separate chromosomes, in this case seed shape, as before, and albumen color, with genes B and b, both loci with complete dominance. In the case of a single trait, the data only showed evidence for rejecting the null hypothesis (Ho) in 1/30 samples, with (P<0.05). In the case of the 30 samples of the two traits experiment, (Ho) was rejected only on 3/30 times, when it was set = 0.05. In both simulations there was a high correspondence between the observed and expected cell frequencies, which is simply due to the fact that (Ho) is true, and under these conditions, that is what would to expect. It was concluded, that Mendel had no reason to manipulate his data in order to make them to coincide with his beliefs. Therefore, in experiment with a single trait, and in experiments with two traits assuming complete dominance, segregation ratios are 3:1; and 9:3:3:1, respectively. Consequently, Mendel”™s laws, under the conditions as were described are absolutely valid and universal.